ANALISIS DESKRIPTIF PENERAPAN BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA MURID KELAS 2 SDI AL AZHAR 25 SEMARANG - Anis Fidiyaningrum; Ngatmini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study is motivated by the existence of problems in students' speaking skills, for example students still tend to be shy (lack of confidence) when asked to speak in front of the class or when asked to answer questions from the teacher. The hope is that every student can have good speaking skills according to their age stage. This study aims to determine the process of applying role-playing in improving speaking skills in grade 2 students of SDI Al Azhar 25 Semarang. This study used descriptive quantitative method, with data collection techniques through observation and documentation. The results showed that with the application of role playing, good results were obtained in the speaking skills of grade 2 students of SDI Al Azhar 25. For the aspect of speaking with clear memorization reached 86.7%, the aspect of speaking with the right intonation reached 81.9%, the aspect of speaking fluently as much as 83.8%, the aspect of speaking with good expression reached 65.7% and the aspect of speaking according to the content of the drama played as much as 81.9%. Based on the results of this study, it is still necessary to conduct further research on speaking with the right expression in speaking skills.